Implementation of Grant Management Policy and Social Assistance for the City of Bekasi - Widodo Indrijantoro; Iwan Irwansyah; Redo Alpha Hernando; Biyan Sukeri (Asian Journal of Applied Business and Management, 2023)
Grant spending must be managed in an orderly manner, in compliance with laws and regulations, efficiently, economically, effectively, transparently and responsibly with due observance of the principles of fairness, decency, rationality and benefits for society. The purpose of this study is to analyze the implementation of management, obstacles and solutions in the management of grants and social assistance based on the Minister of Home Affairs regulation number 32 of 2011. The method used is descriptive qualitative. The results show that the management of grant funds and social assistance at the Bekasi City Regional Financial and Asset Management Agency in 2018 has not been carried out properly. Some of the obstacles to managing grants and social assistance are the lack of staff, staff who have not received training regarding the management of grants, incomplete rules and procedures for managing grants, and overlapping allocations of funds in grant spending.